Analisis Perhitungan Harga Pokok Produksi Dengan Metode Full Costing Sebagai Dasar Penentuan Harga Jual (Studi Kasus Ayam Gepuk Pak Gembus Karawang) - Silawati, Rindy; Haryanto, Vianny Nabiilah (Value : Journal of Management and Business, 2023)
The problem under study this is an analysis of production cost accounts to determine sales price of gepuk pak Gembus Karawang chicken. The research objective is to compare the selling price with company's full cost method. The purpose of this study is to find information about the difference in selling prices between business processes and estimated total costs. Therefore, the research method is qualitative. The data source from which the researcher obtained primary and secondary data using various data collection methods such as interviews, observation, documentation and literature analysis. The results of this study are the price of Pak Gempuk Chicken which is sold for 21,000. However, profits increase under the full cost method. After analyzing the calculation of production costs using the enterprise method and the full cost method, it was found that the calculation of production costs is approx, the gepuk pak Gembus chicken business as the objct of research still uses very simple calculations, even though it is still not detailed. Compotents calculated using the company's method on the gepuk chicken business Pak Gembbus Karawang.